INTRAOPERATIVE NEUROMONITORING AS A METHOD OF MOTOR NERVES FUNCTIONAL VISUALIZATION - P. O. Rumyantsev (Опухоли головы и шеи)
Surgical damage of motor nerves is one of the serious complication which deteriorates patient’s life quality as well as being often a cause of disability. In the article are reflected the methodological aspects of intraoperative neuromonitoring. This method is auxiliary and not substituting the surgical visualization of nerves, but significantly facilitates nerve disclosure as well as functional integrity. Intraoperative neuromonitoring permits to reduce the unintended injury or motor nerves during the operation. This is extremely actual in cases of atypical nerve dispositions, reoperations and when surgery is executed by inexperienced surgeon.